1995
DOI: 10.1540/jsmr.31.129
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Forskolin on Myosin Phosphorylation-Dependent and Independent Contractions in Bovine Tracheal Smooth Muscle.

Abstract: In bovine tracheal smooth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In bovine trachea, it has been reported that forskolin increased cAMP content and inhibited high K + -induced contraction by decreasing Ca 2+ sensitivity of the contractile protein (34). In the present experiments, forskolin also increased cAMP content and inhibited Ca…”
Section: Elucidatedsupporting
confidence: 70%
“…In bovine trachea, it has been reported that forskolin increased cAMP content and inhibited high K + -induced contraction by decreasing Ca 2+ sensitivity of the contractile protein (34). In the present experiments, forskolin also increased cAMP content and inhibited Ca…”
Section: Elucidatedsupporting
confidence: 70%
“…Forskolin (as dry powder capsules) was found to produce bronchodilatation in 16 patients with asthma [82]. A number of studies, using animal models, demonstrated several mechanisms of forskolin to relax pulmonary smooth muscle such as the cAMP-dependent protein kinase (PKA) mediated inhibition of endothelin-1 stimulated generation of inositol phosphates and Ca 2+ mobilization [83], the inhibition of the binding of inositol 1,4,5-triphosphate (IP 3 ) to its Ca 2+ -mobilizing intracellular receptor [84], the protein kinase C isoenzymes mediated activation of large-conductance, calcium-and voltage-activated potassium channels and the resulting pulmonary vasodilatation [85], the decrease in the Ca 2+ oscillation frequency of airway smooth muscle cells by reducing internal Ca 2+ release through IP 3 receptors [86], as well as the inhibition of myosin light chain (MLC) phosphorylation by reducing Ca 2+ influx, Ca 2+ release, by changing the MLC kinase/phosphatase balance and the inhibition of the MLC phosphorylation-independent regulatory mechanism [87]. It has also been reported that the relaxant effects of forskolin in cultured rat tracheal smooth muscle might be mediated, at least in part, by facilitating the sequestration of Ca 2+ into intracellular stores by a mechanism involving guanosine 3′,5′-cyclic monophosphate-dependent protein kinase [88].…”
Section: Forskolinmentioning
confidence: 99%
“…] i level was measured simultaneously with a muscle contraction as reported previously (28). Muscle strips were incubated with PSS containing 5 µM fura2 / AM for overnight at 4°C.…”
Section: +mentioning
confidence: 99%